2022
DOI: 10.3390/pathogens11040409
|View full text |Cite
|
Sign up to set email alerts
|

The Dangerous Liaisons in the Oxidative Stress Response to Leishmania Infection

Abstract: Leishmania parasites preferentially invade macrophages, the professional phagocytic cells, at the site of infection. Macrophages play conflicting roles in Leishmania infection either by the destruction of internalized parasites or by providing a safe shelter for parasite replication. In response to invading pathogens, however, macrophages induce an oxidative burst as a mechanism of defense to promote pathogen removal and contribute to signaling pathways involving inflammation and the immune response. Thus, oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 142 publications
(184 reference statements)
0
10
0
Order By: Relevance
“…The authors showed that treatment with quercetin was able to decrease labile iron in macrophages through the regulation of Nrf2/HO-1 expression, resulting in a decrease in the iron available to the parasite and consequently inducing its death (Cataneo et al, 2019). Although the production of toxic radicals by macrophages (such as ROS and NO) is crucial for the control of infection by intracellular microorganisms, such as Leishmania, the excess of these mediators is also associated with tissue damage and pathogenesis (revised by Bogdan, 2020;Reverte et al, 2022) Several studies have demonstrated the anti-inflammatory effects of quercetin involving the inhibition of nitric oxide production as well as the production of proinflammatory cytokines (Kim et al, 2004;Tsai et al, 2022). In this sense, quercetin appears to be an interesting drug candidate for leishmaniasis since it has both direct antileishmanial activity and the potential to modulate the microbicidal and inflammatory activity of macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…The authors showed that treatment with quercetin was able to decrease labile iron in macrophages through the regulation of Nrf2/HO-1 expression, resulting in a decrease in the iron available to the parasite and consequently inducing its death (Cataneo et al, 2019). Although the production of toxic radicals by macrophages (such as ROS and NO) is crucial for the control of infection by intracellular microorganisms, such as Leishmania, the excess of these mediators is also associated with tissue damage and pathogenesis (revised by Bogdan, 2020;Reverte et al, 2022) Several studies have demonstrated the anti-inflammatory effects of quercetin involving the inhibition of nitric oxide production as well as the production of proinflammatory cytokines (Kim et al, 2004;Tsai et al, 2022). In this sense, quercetin appears to be an interesting drug candidate for leishmaniasis since it has both direct antileishmanial activity and the potential to modulate the microbicidal and inflammatory activity of macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, Ifi202b, also known as IFNactivated gene 202B and encoding for the P202 protein, belongs to the pyrin and HIN domain-containing (PYHIN) proteins, as AIM2 and IFI16 (Wang et al, 2018). In several studies, Ifi202b has been associated with sex differences in autoimmune diseases (Panchanathan et al, 2011;Cao et al, 2018) and this question has recently been addressed in the Leishmania inflammation context (Lockard et al, 2019;Snaka et al, 2022). Likewise, Ifi202b has been shown to be upregulated upon L. major footpad infection in C57BL/6 mice (Ehrchen et al, 2010) and its corresponding P202 protein to exert an inhibitory effect on the AIM2 inflammasome (Wang et al, 2018).…”
Section: Interferon-stimulated Genes and Temporal Expressionmentioning
confidence: 99%
“…One of such processes includes the recognition and ultimately elimination of pathogens. In order to achieve that, macrophages employ a plethora of mechanisms such as oxidative burst, inflammation, or antigen presentation ( Shapouri-Moghaddam et al., 2018 ; Rossi and Fasel, 2018a ; Ferrari, 2019 ; Sheu and Hoffmann, 2022 ; Reverte et al., 2022 ). However, these responses are not always straightforward nor unidirectional as pathogens use different strategies to hijack the macrophage machinery and ultimately exploit it to their advantage.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations